THE EFFECTIVENESS OF HEALTH COUNSELING WITH VIDEO AND LEAFLET MEDIA ON KNOWLEDGE AND ATTITUDE OF STUNTING PREVENTION ON THE MEMBERS OF THE ADOLESCENT COUNSELING AND INFORMATION CENTER (PIKR) - Susanto, Bela Novita Amaris; Zayani, Nofri; Afrioza, Selvy; Nugraha, Deden Gumilar (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Stunting is a problem that cannot be solved in one way, one of which is by improving the quality of youth. The quality of adolescent health is the key to stunting prevention. Stunting can be caused by the health quality of children and adolescents who do not get a balanced nutritional intake. Prevention can be done by providing health education. The purpose of the study was to determine the effect of health education using video media and leaflets on stunting prevention for PIK-R members.Method: The type of research is Pre Experiment Design using the one Group Pretest-Posttest design. The sample consisted of 20 PIK-R members with details of 10 subjects for group 1 with health education treatment with video media and 10 subjects for group 2 with health education treatment with leaflet media. Data analysis using Wilcoxon testResults: The results showed that there was a significant (p<0,05) effect between the level of knowledge with video (p=0,008), knowledge with leaflet (p=0,025), attitudes with video (p=0,008) and attitudes with leaflet (p=0,025) of PIK-R members before and after being given health education using video media and leaflets about stunting prevention.Conclusions: Video media is more effective in increasing the knowledge and attitudes of PIK-R members in Taban Village, Jambe District, Tangerang Regency compared to leaflet media. Adolescents are the main guard in the stunting prevention process, it is necessary to increase understanding about stunting through health education.